Management of patients with metastasis to the vertebrae: recommendations from the Italian Orthopaedic Society (SIOT) Bone Metastasis Study Group. Issue 2 (February 2014) - Gasbarrini, Alessandro; Boriani, Stefano; Capanna, Rodolfo; Casadei, Roberto; Di Martino, Alberto; Silvia Spinelli, Maria; Papapietro, Nicola; Piccioli, Andrea
Abstract : The purpose of this article is to outline the current approach to patients affected by metastasis to the spine and to present a clinical and surgical algorithm available for clinicians and for future research. A modern approach to the patients affected by spinal metastasis in fact requires a multidisciplinary contest where oncologists, radiotherapists, surgeons and physical therapists cooperate with shared vision to provide the best possible integrated treatments available. The authors of this article constitute the Bone Metastasis Study Group of the Italian Orthopaedic Society (SIOT): a national group of orthopedic tumor surgeons who are dedicated to studying the approach, techniques and outcomes of surgery for metastatic tumors of the musculoskeletal system.